2015
DOI: 10.18378/rvads.v10i3.3408
|View full text |Cite
|
Sign up to set email alerts
|

Uso popular de plantas medicinais por mulheres da comunidade quilombola de Furadinho em Vitória da Conquista, Bahia, Brasil

Abstract: Resumo: Objetivou-se com este trabalho realizar um levantamento do uso popular de plantas medicinais por mulheres da Comunidade Quilombola de Furadinho em Vitória da Conquista-Bahia. O trabalho foi realizado na comunidade Quilombola de Furadinho, visando identificar as principais plantas utilizadas com fins medicinais, as formas de obtenção, sua indicação medicinal, a parte da planta utilizada, as formas de preparo, bem como as formas de obtenção e transmissão deste conhecimento. Para a realização dessa pesqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 2 publications
0
10
0
9
Order By: Relevance
“…Plant use by the corporate sector has been facilitated by access to authoritative data on which species are native to Brazil—vital for risk management in sourcing biodiversity inputs (Natura Cosméticos S. A., 2016) and in identification of species occurring naturally on metal‐rich substrates which may have potential for revegetation following mining (Digital Plants, 2020). At the local scale, Reflora resources have been used in research documenting medicinal plant use by women resident in a settlement of descendants of freed slaves (Oliveira, 2015). Traditionally transmitted orally, this knowledge was considered at risk due to migration and lack of interest from young people.…”
Section: Case Studiesmentioning
confidence: 99%
“…Plant use by the corporate sector has been facilitated by access to authoritative data on which species are native to Brazil—vital for risk management in sourcing biodiversity inputs (Natura Cosméticos S. A., 2016) and in identification of species occurring naturally on metal‐rich substrates which may have potential for revegetation following mining (Digital Plants, 2020). At the local scale, Reflora resources have been used in research documenting medicinal plant use by women resident in a settlement of descendants of freed slaves (Oliveira, 2015). Traditionally transmitted orally, this knowledge was considered at risk due to migration and lack of interest from young people.…”
Section: Case Studiesmentioning
confidence: 99%
“…In some communities this species is also of relative importance >1, with values of 1.16, 1.23, and 1.32 in studies by Leite et al (2015) [30], Roque et al (2010) [53], and Oliveira (2015) [29], respectively. This is a species widely distributed in the Caatinga, typical of the Brazilian semiarid, and appreciated for its foraging potential, energy, and medicinal properties [83].…”
Section: Resultsmentioning
confidence: 96%
“…A total of seven articles were used, published between 2014 and 2019 and it was observed that ethnobotany is a knowledge of great relevance for society, especially for quilombola communities. Oliveira (2015) and Reis (2017) point out that the majority of those who know popular knowledge are women, and this information has been perpetuating over time through grandparents who passed it on to their children and so on. However, Santos (2014) warns of an increasingly growing fact, which is the lack of interest of young people in the community in wanting to learn about old knowledge, sometimes because they are attached to new treatments as well as to disbelief by medicinal plants.…”
Section: Resultsmentioning
confidence: 99%